Addressing unmet mental health needs of older adults in Turbo, Colombia: a multi-component psychosocial intervention feasibility study - Giebel, Clarissa; Montoya, Erika; Saldarriaga, Gabriel; Caprioli, Thais; Gabbay, Mark; Martinez, Danicza; Rua, Jessica; Zuluaga, Maria Isabel (International journal for equity in health, 2025)
Older adults have lived through extreme and stressful live events in Colombia, including during the armed conflict. Without adequate mental health resources in place, the aim of this study was to feasibility test a co-produced community-integrated intervention for older adults to improve their mental health and well-being in Turbo, Colombia. Based on a systematic review and meta-analysis of community-based mental health interventions for older adults in LMICs, qualitative interviews with older adults and local stakeholders, as well as a mental health needs assessment survey of the local older adult population in Turbo, Colombia, we consulted older adults in the region to co-produce a community-based intervention. The co-produced intervention ran for three months in 2023, with two sessions provided per week in a community centre (26 sessions in total). The multi-component intervention included social engagement, educational interventions, physical activities, and peer support. Older adults were recruited from the local community. Twelve participants were interviewed about their experiences of the intervention and its feasibility. Eighteen older adults participated in the intervention, with 13 completing the 12 weeks. Attendance rate was high, with 10 participants attending between 90 to 100% of all 26 sessions. Qualitative interviews with 12 participants showed that participants valued the intervention and the activities it offered, that the intervention was feasible, and expressed a keen interest for the intervention to be continued. This co-produced and evidence-based intervention for older victims of 'La Violencia' in Colombia has the potential to provide affordable, acceptable and relevant community-based resources supporting mental health and wellbeing within the community; providing care and support with trained facilitation. Normally, this group would not be able to access services to address their social and psychological isolation and distress. In light of limited mental health support across LMICs, this intervention could provide mental health for older adults in other communities in Colombia and elsewhere developed through co-production, cultural adaptation, subject to further evaluation.